1996
DOI: 10.1007/bf02265273
|View full text |Cite
|
Sign up to set email alerts
|

Clonality of tuberous sclerosis harmatomas shown by non-random X-chromosome inactivation

Abstract: Tuberous sclerosis (TSC) is an autosomal dominant condition characterised by tumour-like malformations (hamartomas) in the brain and other organs. A proportion of hamartomas from patients with TSC show loss of heterozygosity (LOH) for DNA markers in the region of either the TSC1 gene on chromosome 9q34 or the TSC2 gene on 16p13.3. This implies that these lesions are clonal. We have studied X-chromosome inactivation, as a marker of clonality, in 13 hamartomas from females with TSC. The hamartomas comprised five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(41 citation statements)
references
References 13 publications
1
39
0
1
Order By: Relevance
“…Ozolek et al on the other hand described loss of heterozygosity rates (fractional allelic losses) for REAH that are intermediate between inflamed mucosa and sinonasal adenocarcinoma and suggested that it may represent a benign neoplasm [9]. This would be in keeping with the finding of a neoplastic origin for many other so-called hamartomas in the body, such as angiomyolipoma of the kidney [10]. Jo et al [11] have suggested that REAH and the related seromucinous hamartomas (see below), may be more accurately designated as ''adenomas'', reflecting this possible neoplastic nature.…”
Section: Respiratory Epithelial Adenomatoid Hamartomamentioning
confidence: 84%
“…Ozolek et al on the other hand described loss of heterozygosity rates (fractional allelic losses) for REAH that are intermediate between inflamed mucosa and sinonasal adenocarcinoma and suggested that it may represent a benign neoplasm [9]. This would be in keeping with the finding of a neoplastic origin for many other so-called hamartomas in the body, such as angiomyolipoma of the kidney [10]. Jo et al [11] have suggested that REAH and the related seromucinous hamartomas (see below), may be more accurately designated as ''adenomas'', reflecting this possible neoplastic nature.…”
Section: Respiratory Epithelial Adenomatoid Hamartomamentioning
confidence: 84%
“…AMLs have been regarded as hamartomas; however, clonality assays performed in a recent study of renal AMLs has shown the myoid and the vascular components to be monoclonal, implying a neoplastic proliferation (15,16). The adipose tissue component of the AML was found to be polyclonal and the authors speculate that the fat is metaplastic or a reactive change in the neoplasm.…”
Section: Discussionmentioning
confidence: 96%
“…Attempts to demonstrate a second-hit mutation in TSC skin tumors were mostly negative, and loss of heterozygosity (LOH) at the TSC1 or TSC2 locus was observed in only a few TSC skin tumors. 47,58,[73][74][75] Inability to detect LOH in most samples was likely due to the cellular heterogeneity of these tumors. This problem was surmounted by using fluorescence in situ hybridization to analyze individual nuclei, which documented allelic deletion for TSC2 in dermal touch preparations of 8=8 angiofibromas and 6=7 periungual fibromas.…”
Section: Cellular Composition Of Tsc Skin Tumorsmentioning
confidence: 99%